AMBANK GROUP CHAIRMAN LAUNCHES AZMAN HASHIM USM SPORTS ARENA - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, November 2015 – Founder and Chairman of AmBank Group, Tan Sri Azman Hashim recently unveiled the Azman Hashim USM Sports Arena at Universiti Sains Malaysia (USM).